2016
DOI: 10.1007/s10048-016-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Cortical gene expression: prognostic value for seizure outcome following temporal lobectomy and amygdalohippocampectomy

Abstract: Whole genome analyses were performed to test the hypothesis that temporal cortical gene expression differs between epilepsy patients rendered seizure-free versus non-seizure-free following anterior temporal lobectomy with amygdalohippocampectomy (ATL/AH). Twenty four patients underwent ATL/AH to treat medically intractable seizures of temporal lobe origin (mean age 35.5 years, mean follow up 42.2 months), they were then dichotomized into seizure-free and non-seizure-free groups. Tissue RNA was isolated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Most biomarkers, however, are continuous variables (e.g., plasma miRNA levels), and a cutoff value must be defined to determine whether or not a condition is present. Many recent studies have attempted to define "multivariate biomarker signatures", e.g., a combinatory biomarker, reporting on molecular tissue microenvironment (Gallek et al, 2016), multistructure magnetic resonance imaging (MRI) abnormalities (Pitkänen and Immonen, 2014), combined imaging and behavioral abnormalities (Pascente et al, 2016), or combined behavioral abnormalities (Bröer and Löscher, 2015). Although combinatory biomarkers can be useful in some conditions (e.g., response biomarkers), standardization and setting the cutoff values for combinatory biomarker panels is a challenge, as is translation from the laboratory to the clinic.…”
Section: Biomarker Discovery Process and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most biomarkers, however, are continuous variables (e.g., plasma miRNA levels), and a cutoff value must be defined to determine whether or not a condition is present. Many recent studies have attempted to define "multivariate biomarker signatures", e.g., a combinatory biomarker, reporting on molecular tissue microenvironment (Gallek et al, 2016), multistructure magnetic resonance imaging (MRI) abnormalities (Pitkänen and Immonen, 2014), combined imaging and behavioral abnormalities (Pascente et al, 2016), or combined behavioral abnormalities (Bröer and Löscher, 2015). Although combinatory biomarkers can be useful in some conditions (e.g., response biomarkers), standardization and setting the cutoff values for combinatory biomarker panels is a challenge, as is translation from the laboratory to the clinic.…”
Section: Biomarker Discovery Process and Statisticsmentioning
confidence: 99%
“…One of the studies listed in Table 3 can be considered to fall into the predictive biomarker category. Gallek et al (Gallek et al, 2016) found that a relative downregulation of a set of genes in the lateral temporal cortex serves as a predictive biomarker for seizure-freedom after epilepsy surgery (Table 3).…”
Section: Predictive Biomarkersmentioning
confidence: 99%
“…Our differential expression (DE) data were obtained through the use of RNA-Seq, a next generation sequencing (NGS) method with improved sensitivity and dynamic range compared with microarray-based profiling 10 . Based on our results, we reiterate the concept of “neurosurgical genomics” whereby systemic leukocyte gene expression serves as a prognostic biomarker for successful outcome from operative neurosurgical intervention 11 .…”
Section: Introductionmentioning
confidence: 59%
“…All patients met the Task Force of the ILAE (International League Against Epilepsy) Commission on Therapeutic Strategies definition of drug-resistant epilepsy. Therefore, each patient had “intractable epilepsy” resistant to at least two well tolerated, appropriately chosen and prescribed anti-epileptic drug regimens either as mono-therapies or in combination 11,48 . This study was approved by and conducted in accordance with the approved protocols and subject consent forms provided by the University of Arizona College of Medicine Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…It had been reported that there is a relative reduction in ZNF852, CDCP2, PRRT1, FLJ41170, and 7RNA probes in patients who become seizure-free, after lobectomy for interactable TLE patients [ 224 ]. An amplified hippocampal myoinositol/total creatine ratio is a potential diagnostic biomarker for epileptogenesis in the case of lithium–pilocarpine-induced status epilepticus [ 105 ].…”
Section: Biomarkers Associated With Diagnosis Of Epileptogenesismentioning
confidence: 99%